Meconium aspiration syndrome: challenges and solutions - Goel A; Nangia S (Dove Medical Press, 2017)
Ankita Goel, Sushma Nangia Department of Neonatology, Lady Hardinge Medical College and Kalawati Saran Children Hospital, Shaheed Bhagat Singh Marg, New Delhi, India Abstract: Meconium aspiration syndrome (MAS) is an important cause of morbidity and mortality among term newborns. A result of antepartum or postpartum aspiration of meconium stained amniotic fluid (MSAF), MAS causes respiratory distress of varying severity, often complicated by air leaks or persistent pulmonary hypertension (PPHN). There has been a tremendous change in the concepts of pathophysiology and management of MAS over the last few decades. Routine endotracheal suctioning is no longer recommended in both vigorous and nonvigorous neonates with MSAF. Supportive management, along with newer therapies such as surfactant, inhaled nitric oxide, and high-frequency ventilation, has resulted in marked improvement in the overall outcome of MAS. The present review highlights the challenges in understanding the complex pathophysiology and optimal management approach to MAS. Potential future therapies and drugs in trial are also discussed briefly. Keywords: meconium aspiration syndrome, endotracheal suction, surfactant, inhaled nitric oxide, high-frequency ventilation, persistent pulmonary hypertension